Pengaruh Penambahan Wortel (Daucus carota L) terhadap Karakteristik Kimia dan Organoleptik Sosis Ikan Tongkol (Euthynnus affinis) - Adhan Labatjo; Rahim Husain; Fernandy M. Djailani (Transbahasa, 2026)
Mackerel tuna is known for its high protein content, however, its utilization remains limited and lacks diversification. One form of product diversification is the processing of mackerel tuna into sausage. The addition of food ingredients, such as carrots, can enhance the nutritional value, particulary vitamin A content, and improve the product’s physical and organoleptic characteristics. This study aims to determine the influence of carrot addition on the chemical and organoleptic properties of mackerel tuna sausage. The method employed was an experimental design using a Completely Randomized Design (CRD) with three treatment levels of carrot addition (60g, 70g, and 80g), each with several replications. The observed parameters included moisture content, protein content, vitamin A content, and organoleptic evaluation covering tasta, aroma, texture, and color. The findings showed that the moisture content at 60g treatment was 72.93%, at 70g was 74.04%, and at 80g was 74.65%. the protein content at 60g treatment was 11.97%, at 70g was 12.07%, and at 80g was 13.14%. These findings indicate that both moisture and protein content increased across all treatments. The organoleptic test result revealed that the best treatment was the addition of 80g of carrot, which was preferred by the panelists for taste, aroma, texture, and color. In conclusion, the addiotion of carrot improves the chemical and organoleptic quality of mackerel tuna sausage. Therefore, carrots can be atilized as an additive ingredient to enhance the nutritional value and overall quality of processed fish products.